Strategi Istana Maimun Sebagai Ikon Pariwisata Kota Medan - Irma Yusriani Simamora; Arofah Sri Mulyani Mz; Irma Yanti Lubi; Nabillah Miftahul Jannah; Abdillah Taufiqurrahman (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
Maimun Palace is a historic building built during the 9th Malay Sultan Deli Dynasty or Sultan Ma'moen Al Rasyid Perkasa Alamsyah. Construction of this building began on 26 August 1888 and ended on 18 May 1891. Maimun Palace is the Palace of the Deli Sultanate which is one of the tourism icons located in Medan City, North Sumatra. This research uses qualitative methods which can be obtained through observation of the palace. Maimun, the aim of this research is to find out how the Maimun Palace is said to be a tourism icon and to identify strategies for the Maimun Palace as a tourism icon for the city of Medan. The results of this research show that the Maimun Palace is said to be a tourism icon for the city of Medan because the main attraction of the Maimun Palace lies in its architecture. There is a combination of several cultures that influence the appearance of the Maimun Palace. Making the Maimun Palace an icon of the city of Medan because of its lack of natural potential, through nature reserves (heritage) it can increase tourism in Indonesia. So, in order to increase tourism potential in the city of Medan, Maimun Palace was made an icon of the city of Medan.